The novel dual BET/HDAC inhibitor TW09 mediates cell death by mitochondrial apoptosis in rhabdomyosarcoma cells. (28th August 2020) - Laszig, Stephanie; Boedicker, Cathinka; Weiser, Tim; Knapp, Stefan; Fulda, Simone
Abstract: Targeting the epigenome of cancer cells with the combination of Bromodomain and Extra Terminal (BET) protein inhibitors and histone deacetylase (HDAC) inhibitors has shown synergistic antitumor effects in several cancer types. In this study, we investigate the antitumor potential of the novel dual BET/HDAC inhibitor TW09 in rhabdomyosarcoma (RMS) cells. TW09 reduces cell viability, suppresses long-term clonogenic survival and induces cell death in RMS cells in a dose-dependent manner. Compared to BET/HDAC co-inhibition using JQ1 and MS-275, TW09 induces similar cell death at equimolar concentrations and regulates BET and HDAC target proteins (e.g. c-MYC, H3 acetylation). Mechanistic studies revealed that TW09 upregulates BIM, NOXA, PUMA and BMF, while downregulating BCL-XL, leading to proapoptotic rebalancing of BCL-2 proteins. This results in BAK and BAX activation and caspase-dependent apoptosis, since individual genetic silencing of BIM, NOXA, PUMA, BMF, BAK or BAX, overexpression of BCL-2 or the caspase inhibition with zVAD.fmk all rescue JQ1/BYL719-induced cell death. In conclusion, TW09 shows potent antitumor activity in RMS cells in vitro by inducing mitochondrial apoptosis and may represent a promising new therapeutic option for the treatment of RMS. Graphical abstract: Image 1 Highlights: TW09 triggers mitochondrial apoptosis in rhabdomyosarcoma cells. TW09 inhibits c-Myc and induces H3 acetylation. TW09 upregulates BIM, NOXA, PUMA and BMF, while downregulating BCL-XL . Silencing of BIM, NOXA, PUMA or BMF rescues TW09-induced apoptosis. Overexpression of BCL-2 protects from TW09-induced apoptosis.